2022
DOI: 10.1177/20416695221078878
|View full text |Cite
|
Sign up to set email alerts
|

Partially Separable Aspects of Spatial and Temporal Estimations in Virtual Navigation as Revealed by Adaptation

Abstract: Recent studies claim that estimating the magnitude of the spatial and temporal aspects of one's self-motion shows similar characteristics, suggesting shared processing mechanisms between these two dimensions. While the estimation of other magnitude dimensions, such as size, number, and duration, exhibits negative aftereffects after prolonged exposure to the stimulus, it remains to be elucidated whether this could occur similarly in the estimation of the distance travelled and time elapsed during one's self-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…Single-cell recordings in non-human primates and fMRI studies in humans also indicate the presence of ratioselective neurons in the prefrontal and parietal cortex, regions often associated with the processing of absolute magnitudes [58,59]. By contrast, behavioural studies on cross-dimensional adaptation between space, time and numerosity found null or asymmetrical effects, indicating (partially) separate encoding mechanisms for different magnitudes [60][61][62]. Therefore, a modified view of ATOM might be that absolute magnitudes are initially encoded by (partially) separate mechanisms but are transformed into abstract relative magnitudes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell recordings in non-human primates and fMRI studies in humans also indicate the presence of ratioselective neurons in the prefrontal and parietal cortex, regions often associated with the processing of absolute magnitudes [58,59]. By contrast, behavioural studies on cross-dimensional adaptation between space, time and numerosity found null or asymmetrical effects, indicating (partially) separate encoding mechanisms for different magnitudes [60][61][62]. Therefore, a modified view of ATOM might be that absolute magnitudes are initially encoded by (partially) separate mechanisms but are transformed into abstract relative magnitudes (i.e.…”
Section: Discussionmentioning
confidence: 99%